2014
DOI: 10.1590/s1982-56762014000100008
|View full text |Cite
|
Sign up to set email alerts
|

EF-1α gene and IGS rDNA sequencing of Fusarium oxysporum f. sp. vasinfectum and F. oxysporum f. sp. phaseoli reveals polyphyletic origin of strains

Abstract: The fungi Fusarium oxysporum f. sp. vasinfectum (Fov) and F. oxysporum f. sp. phaseoli (Fop) are important pathogens that cause wilt on cotton and common bean, respectively. In the present study, phylogenetic trees constructed with partial sequences of the translation elongation factor gene and ribosomal intergenic spacer region of Brazilian Fov and Fop strains revealed polyphyletic origin of strains within both formae speciales. This creates an obstacle for the development of specific molecular diagnostic met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…The F1 fragment was firstly used in the Elata Clade of the genus Morchella for population studies and some potential hybridization or gene transfer events were revealed in several species (Du et al 2016). The phylogeny of intergenic spacer region (IGS) was reported to conflict with the phylogeny of EF1-a in the genus Fusarium (Mbofung et al 2006;Silva et al 2014). By comparing the reproductive (MAT1-1-1 and MAT1-2-1) and the non-reproductive (F1 and IGS) datasets, we tested whether the conflicts are inherent only to the reproductive genes or they also exist in other parts of the genome in species of the Esculenta Clade.…”
Section: Conflicts Between Non-reproductive Genes (F1 and Igs) And Thmentioning
confidence: 99%
“…The F1 fragment was firstly used in the Elata Clade of the genus Morchella for population studies and some potential hybridization or gene transfer events were revealed in several species (Du et al 2016). The phylogeny of intergenic spacer region (IGS) was reported to conflict with the phylogeny of EF1-a in the genus Fusarium (Mbofung et al 2006;Silva et al 2014). By comparing the reproductive (MAT1-1-1 and MAT1-2-1) and the non-reproductive (F1 and IGS) datasets, we tested whether the conflicts are inherent only to the reproductive genes or they also exist in other parts of the genome in species of the Esculenta Clade.…”
Section: Conflicts Between Non-reproductive Genes (F1 and Igs) And Thmentioning
confidence: 99%
“…One of these patients presented isolates of 2 different species one of which was related to the environmental isolates (F.oxysporum). We believe that the typing method used in our study was discriminatory [14,22].…”
Section: Discussionmentioning
confidence: 67%
“…Molecular identification of Fusarium species complex and species were performed by sequencing the internal transcribed spacer (ITS) region of ribosomal DNA [29] and the elongation factor 1 alpha (EF-1α) gene, respectively [30]. Mycelia were produced by inoculating microconidia of clinical isolates into Sabouraud-dextrose broth media and incubated at 28 ‱ C at 120 rpm (MAX Q 4000 Benchtop Orbital Shaker Incubator (Thermo Fisher Scientific, Waltham, MA, USA) for 3 days.…”
Section: Molecular Identification Of Fusarium Sppmentioning
confidence: 99%
“…The polymerase chain reactions (PCR) amplifications were carried out with TransTaq Âź DNA Polymerase High Fidelity (TransGen Biotech, Beijing, China) and primers ITS1 (5 TCC GTA GGT GAA CCT GCG G 3 ) and ITS4 (5 TCC TCC GCT TAT TGA TAT GC 3 ) [29]; and EF-1α forward (5 ATG GGT AAG GA(A/G) GAC AAG AC 3 ) and EF-1α reverse (5 GGA (G/A)GT ACC AGT (G/C)AT CAT GTT-3') [30]. Purified PCR products were sequenced with the respective primers in ABI 3730 DNA Analyzer (Life Technologies-Applied Biosystems, Waltham, MA, USA).…”
Section: Molecular Identification Of Fusarium Sppmentioning
confidence: 99%
See 1 more Smart Citation